Direct shear behavior of castellated dry RPC joints in precast concrete segmental bridges. (October 2021) - Jiang, Haibo; Huang, Chengwang; Feng, Jiahui; Gao, Xingjun; Wang, Tianlong; Zhong, Zucai
Abstract: Reactive power concrete (RPC) is advanced cementitious material. Precast RPC segmental bridges (PRSBs) have been popular in China. The shear behavior of the dry RPC joints between concrete segments in PRSBs was the most concerning issue. Ten push-off specimens were tested under direct shear with parameters of key number, confining stress, and steel fiber type. The cracking patterns, failure modes, and load–displacement curves of the dry RPC joints were obtained. Experimental analysis indicated that confining stress could significantly improve the cracking resistance and shear capacity of specimens, which the influence on three-keyed joints was higher than that of single-keyed joints and monolithic specimens. The normalized cracking shear stress and the normalized ultimate shear stress transferred across the keyed-joints decreased with the increasing of key numbers, but this effect was annihilated as the confining stress increased. The concrete strength could significantly affect the shear capacity of joints, where the shear strength of dry RPC joints was about 2.38 ~ 3.17 times that of dry normal concrete (NC) joints. The steel fiber type had a slight influence on the shear strength of dry RPC joints. According to the comparison between experimental results and predictions obtained by several typical formulae, the existing formulae could not well predict the shear capacity of dry RPC joints. A more accurate formula considering the tensile strength of concrete was proposed to predict the shear strength of the dry RPC joints in PRSBs, which the mean ratio of calculated value to test results was 0.995, and the standard deviation was 0.123.